Kak uchityvat tipologiccheskie osobennosti podrostkov pri podgotovke prygunov s shestom Kak uchityvat' tipologicheskie osobennosti podrostkov pri podgotovke prygunov s shestom - Kovalchuk, G. I.; Vasnev, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
To reveal the opportunities of complex-typological approach's realization in the process of youngpole-jumpers coaching was the purpose of this study. 25 pole-jumpers aged 13-14 acted as subjects. The somatotypical, dermatoglific, physical fitness, biomechanical and psycho- diagnosis indicators of the teenagers pole-jumpers had been analysed. The young athletes of the muscular-toracal somatotype, labil nervous system, respectively slow rates of maturation, demonstrating the above everage values of physical preparadeness and motorics indicies are more successful in sports activity. The evaluation of the biological age allowes to correct the volume and intensivity of the training loadings.